Cellulose-assisted combustion synthesis of Li4Ti5O12 adopting anatase TiO2 solid as raw material with high electrochemical performance - Yuan, T.; Wang, K.; Cai, R.; Ran, R.; Shao, Zongping (Elsevier B.V., 2009)
Pure-phase spinel-type lithium titanate, Li4Ti5O12, was successfully fabricated by cellulose-assisted glycine-nitrate (cellulose-GN) combustion process at reduced temperature using anatase TiO2 solid as raw material of titanium. The influence of cellulose and impregnation sequence on the phase purity, particle size and electrochemical performance of Li4Ti5O12 was investigated. The sequence of preparation was found to have big effect on the phase formation and electrochemical performance of the oxides. High-purity and well-crystallized Li4Ti5O12 oxides were obtained at a calcination temperature of 750 °C via the sequence III, for which the cellulose was first adsorbed by the mixed solution of LiNO3 and glycine followed by the impregnation of TiO2 suspension. Compared with solid-state reaction, the cellulose-GN process produced the Li4Ti5O12 oxides with smaller particle size and higher specific capacity due to the lower synthesis temperature. A reversible capacity of 103 mAh/g at 20 C rate and fairly stable cycling performance even at 40 C was achieved. © 2008 Elsevier B.V. All rights reserved.